Does psychological distress directly increase risk of incident cardiovascular disease? Evidence from a prospective cohort study using a longer-term measure of distress - Emily Banks; Rosemary J Korda; Grace Joshy; Peter Butterworth; Lyndall Strazdins; Jennifer Welsh (BMJ Open)
Objective Cardiovascular disease (CVD) incidence is elevated among people with psychological distress. However, whether the relationship is causal is unclear, partly due to methodological limitations, including limited evidence relating to longer-term rather than single time-point measures of distress. We compared CVD relative risks for psychological distress using single time-point and multi-time-point assessments using data from a large-scale cohort study.Design We used questionnaire data, with data collection at two time-points (time 1: between 2006 and 2009; time 2: between 2010 and 2015), from CVD-free and cancer-free 45 and Up Study participants, linked to hospitalisation and death records. The follow-up period began at time 2 and ended on 30 November 2017. Psychological distress was measured at both time-points using Kessler 10 (K10), allowing assessment of single time-point (at time 2: high (K10 score: 22–50) vs low (K10 score: <12)) and multi-time-point (high distress (K10 score: 22–50) at both time-points vs low distress (K10 score: <12) at both time-points) measures of distress. Cox regression quantified the association between distress and major CVD, with and without adjustment for sociodemographic and health-related characteristics, including functional limitations.Results Among 83 906 respondents, 7350 CVD events occurred over 410 719 follow-up person-years (rate: 17.9 per 1000 person-years). Age-adjusted and sex-adjusted rates of major CVD were elevated by 50%–60% among those with high versus low distress for both the multi-time-point (HR=1.63, 95% CI 1.40 to 1.90) and single time-point (HR=1.53, 95% CI 1.39 to 1.69) assessments. HRs for both measures of distress attenuated with adjustment for sociodemographic and health-related characteristics, and there was little evidence of an association when functional limitations were taken into account (multi-time-point HR=1.09, 95% CI 0.93 to 1.27; single time-point HR=1.14, 95% CI 1.02 to 1.26).Conclusion Irrespective of whether a single time-point or multi-time-point measure is used, the distress–CVD relationship is substantively explained by sociodemographic characteristics and pre-existing physical health-related factors.